Flow of non-Newtonian fluid through a permeable artery having non-uniform cross section with multiple stenosis - Prasad, K. Maruthi; Yasa, Prabhaker Reddy (Journal of Naval Architecture and Marine Engineering, 2020)
In this paper, the effect of slip on Micropolar fluid in a circular tube of non-uniform cross-section with multiple stenosis have been studied. The coupled equations governing to the flow are calculated by using Homotopy Perturbation Method. The effects of various parameters with heights of the stenosis on the resistance to the flow and wall shear stress have been studied by deriving the expressions for the flow characteristics and their solutions have been obtained. It is found that the resistance to the flow increases with the heights of the stenosis, inclination, Thermophoresis parameter, local temperature Grashof number, local nanoparticle Grashof number, inclination and permeability constant and decreases with Brownian motion parameter. It is found that the shear stress at the wall increases with heights of the stenosis, Brownian motion parameter but decreases with local nanoparticle Grashof number, Thermophoresis parameter and permeability constant. Also, it is observed that the volume of the bolus increases with the increase of permeability constant.